Tourism Village Development Strategy through Community-Based Tourism and Women’s Empowerment for Sustainable Development in Bakau Serip. - Anggraini, Ratih; Arianto, Hepy Hefri; Putra, Edy Yulianto; Nainggolan, Ferdinand; Sudhartio, Lily; Purwianti, Lily; Setyawan, Agustinus; Aliandrina, Dessy; Chandra, Budi; Ivone, Ivone (ConCEPt - Conference on Community Engagement Project, 2024)
This study focuses on the development strategy of tourism villages through the implementation of Community Based Tourism (CBT) and women's empowerment as an effort to achieve Sustainable Development Goals (SDGs) in Kampung Tua Bakau Serip, Nongsa District. Tourism villages are crucial drivers of sustainable economic and environmental development in Indonesia, yet challenges remain in optimizing human resources and managing village potential. Through partnerships between Batam International University, local communities, and corporate social responsibility (CSR) programs, various capacity-building initiatives were implemented, particularly emphasizing women's participation in creative economy activities. The development roadmap envisions Kampung Tua Bakau Serip as a "Smart Village" and Mangrove Education Study Center over the next five years. Initial results indicate that community empowerment, infrastructure improvement, and educational tourism development can significantly contribute to economic growth and environmental conservation. The research highlights the importance of sustainable community engagement in achieving long-term tourism village viability.